Management of Locked Posterior Shoulder Dislocation with Reverse Hill–Sachs Lesions via Anatomical Reconstructions. Issue 7 (11th October 2021) - Mi, Meng; Zhang, Jin‐ming; Jiang, Xie‐yuan; Huang, Qiang
Abstract : Objective: To evaluate the outcomes of locked posterior shoulder dislocation with reverse Hill–Sachs lesions in patients treated with anatomical reconstructions. Methods: Patients who were treated at our institution between January 2016 and June 2020 were retrospectively reviewed. The demographics of the patients including gender, age, occupation, and dominant arm were recorded. Eleven cases from 10 patients qualified in this study. Nine males and one female were included. The mean age of the patients was 44.8 years (range, 33–54 years). Mechanism of injury, duration between injuries and definitive diagnosis, misdiagnosis, size of humeral head impaction, treatment maneuver, and details of operation performed were reviewed. Plain radiographs and computed tomography (CT) scan were taken to determine the size of defects preoperatively and fracture healing during follow‐up. During surgery, the deltopectoral approach was employed. Anatomical reconstruction procedure including reduction, disimpaction, bone grafting, and fixation were sequentially performed. Either cancellous autograft from iliac crest or allograft were used and the fractures were anatomically reduced and stabilized by screws or plates. Visual Analog Scale (VAS) and Constant–Murley score were recorded to determine the functional outcomes preoperatively, at 3 months and 6 months postoperatively, and at the last follow‐up. The range of motion in forward flexion was recorded at 6 months follow‐up postoperatively. Results: Causes of injuries included epileptic seizure in four cases, fall in three cases, and road traffic accident in three cases. Misdiagnoses occurred in five out of 10 patients. The mean time between injury and definitive treatment among those misdiagnosed was 112 days. The mean size of the impacted reverse Hill–Sachs lesions was 33.95% (range, 19.1%–42.6%). All patients received surgical management with anatomical reconstruction approach, including open reduction, disimpaction, bone grafting, and internal fixation. The mean amount of bleeding during operation was 450 mL. The mean follow‐up period was 22.6 months. Fracture healing was observed by 8 weeks in all cases postoperatively and evidence of bone grafting could not be further detected on CT scan at 6 month during follow‐up. VAS was significantly lower at the last follow‐up (0.68 ± 0.21) in comparison to preoperative scores (4.96 ± 0.97) ( P  < 0.05). Constant–Murley was improved significantly at the last follow‐up (91.7 ± 8.3) in comparison to that preoperatively (40.6 ± 10.3) ( P  < 0.05). The mean range of motion in forward flexion was 38.25° ± 9.36° preoperatively and significantly improved to 162.48° ± 12.68° at 6‐month follow‐up ( P  < 0.05). Conclusion: The anatomical reconstruction procedure by open reduction and bone augmentation for the treatment of locked posterior shoulder dislocation with reverse Hill–Sachs lesion was promising in both fracture healing and functional outcomes. Abstract : Fracture healing after treatment of locked posterior shoulder dislocation with reverse Hill–Sachs lesion via anatomical reconstructions.